149k views
2 votes
converting to slope intercept formmatch each equation to an equivalent equation written in slope intercept form.

converting to slope intercept formmatch each equation to an equivalent equation written-example-1
User Chinthana
by
5.5k points

1 Answer

7 votes

Statement Problem: Match each equation to an equivalent equation written in slope-intercept form.

Solution:

A slope intercept form equation is written as;


y=mx+b

(a)


2y-6=x

Add 6 to both sides of the equation;


\begin{gathered} 2y-6+6=x+6 \\ 2y=x+6 \end{gathered}

Divide each term by 2;


\begin{gathered} (2y)/(2)=(x)/(2)+(6)/(2) \\ y=((1)/(2))x+3 \end{gathered}

(b)


undefined

User Rubndsouza
by
5.2k points